Manajemen Pengelolaan Khutbah Jum’at Di Masjid Baitul Ihsan Bank Indonesia Surabaya - Qisam, Shobikhul; Herma Musyanto, Muhammad; Nugroho, Adityo; Mauludi, Mauludi (MADINAH, 2019)
The purpose of this research is to know the production process in the Friday sermon program at the Baitul Ihsan Bank Indonesia Surabaya mosque. This type of research is qualitative research and is located at Baitul Ihsan Bank Indonesia Mosque in Surabaya. The research approach used is a descriptive case study approach. Data sources in this study are primary data sources totaling 3 informants. Data collection techniques used in this study are: observation, interview and documentation techniques. The results showed that the production process of the Friday sermon program at the Baitul Ihsan Bank Indonesia Surabaya mosque was in accordance with the program development. This study also produced three findings. First, related to the initial idea of ​​the program. Second, an overview of the selection and selection of preachers and SOP for program implementation. Third, an overview of the program's final design. The implications of this research need to reinforce the SOP on the implementation of the Friday sermon program as well as the Friday sermon theme at the Baitul Ihsan Mosque in Bank Indonesia Surabaya and hold documentation and publications on Friday sermon activities.